Combination of natural strategies to improve the oxidative stability of echium seed oil. Issue 2 (14th January 2021) - Roschel, Gabriela Grassmann; da Silveira, Tayse Ferreira Ferreira; Cajaíba, Letícia Maeda; Ferrari, Roseli Aparecida; Castro, Inar Alves
Abstract : Abstract: Echium seed oil is an alternative source of omega 3 fatty acids but it is highly susceptible to oxidation. A combination of three natural strategies was proposed in this study aiming to improve the oxidative stability of echium oil obtained by pressing (PO) or solvent extraction (PSO), kept in the storage condition for 180 days or during the consumption for 30 days. Our results showed that the reduction of temperature was sufficient to keep the oil stable during storage for both samples. During the consumption time, the best stability was achieved by adding a mixture of antioxidants, composed of sinapic (500 ppm), ascorbic (250 ppm), and citric (150 ppm) acids, and/or 20% of high oleic sunflower oil. The combined strategies promoted a 34 to 80% reduction of peroxide value and 0 to 85% reduction of malondialdehyde concentrations in the samples, showing to be a feasible and natural alternative to improve the oxidative stability of echium oil. Practical Application: Our study successfully applied an optimized combination of simple and low‐cost strategies to enhance the chemical stability of echium seed oil. As the use of echium oil expands around the world, the oil industry and final consumers may benefit from our results to increase the oil shelf‐life.